Technologies of Information and Communication Applied to Water Management: The Case of the Bogota River - Güiza-Suarez, Leonardo (2020)
[Introduction]: Taking into account the magnitude of water-related environmental problems and phenomena such as droughts and floods, intensified by climate change, it is useful to take advantage of new technologies, through the development of virtual environmental observatories. [Objective]:  This article presents the experience of the Environmental Regional Observatory and Development Sustainable of the Bogota River (ORARBO), from their motivations until its implementation. [Methodology]: To show this, it is provided the theoretical, methodological and practical elements taken into account to contribute to its replication in similar social, cultural and environmental contexts in Latin America. [Results]: A theoretical analysis between the contribution of the information technologies and communications (ICT) to water and governance management and the practical experience gained in its execution in Colombia. [Conclusion]: It is concluded that the ICT can strengthen the comprehensive water management, by facilitating access to information and participation in environmental issues and in this way increase the incidence in the decisions to face this important issue.